Innovative solutions for the wine sector: The role of startups - Roberta Spadoni; Mattia Nanetti; Antonio Bondanese; Sergio Rivaroli (Wine Economics and Policy, 2019)
The economic globalisation has opened new pathways for commerce and triggered a logistical revolution, which in turn has produced enormous technological innovations. In this context, the role of startups is becoming increasingly crucial since they are positioning themselves as innovation enablers among large and small companies. Between these innovations, IoT, Big Data Analytics and Blockchain can be used in various domains, among which the logistics of the whole wine supply chain. Here we will consider some of the issues and needs that arise in this market sector, showing how Wenda - a startup born in Bologna in February 2015 that works to improve sustainability and traceability in Food & Beverage supply chains - has been able to leverage IoT, Big Data Analytics and Blockchain to empower the wine supply chain with solutions that enable wine traceability throughout the distribution and the after-buying-in preservation and commercialisation phases.
Keywords: 330; Wine; Innovations; Supply chain; IoT; Big data; Startups